A Rare Clinical Presentation of Giant Bilateral Labial Fibroepithelial Stromal Polyps in Patient with Psoriasis Disease. (26th January 2016) - Avsar, Ayse Filiz; Islek, Elcin; Yildirim, Melahat; Ahsen, Hilal
Abstract : Fibroepithelial polyps (FEPs) are rarely seen lesions of the lower female genital tract with polypoid proliferations of stroma. These tumors usually present in the vulvovaginal region of the reproductive aged women. In this presentation, we report a case of a psoriatic woman who developed unusual multiple polypoid lesions approximately 15 cm in size arising from both left and right labia minora and unique connection of FEPs with psoriasis disease.